Evaluation of the effects of using 3D - patient specific models of displaced intra - articular calcaneal fractures in surgery. (October 2022) - Ozturk, Anil Murat; Ozer, Mehmet Asim; Suer, Onur; Derin, Okan; Govsa, Figen; Aktuglu, Kemal
Highlights: To make surgery with assisting 3D printing model will decrease the duration of the operation, blood loss volume, fluoroscopy usage, instrumentation time. Both surgery types restored Bohler angle, Gissane angle, calcaneal width and calcaneal facet height after operation significantly ( p < 0.0001). To perform the surgery with assisting the 3D model surgery is more beneficial to protect achieved post-op. restoration in long follow-up compared to the conventional surgery. Both surgery types are successful in functional scores at follow-up. Resident doctors have more positive perceptions about 3D model. Using 3D printing technology in open reduction and fixation for calcaneal fractures is a feasible, accurate, and effective technique leading to improved patient-specific preoperative planning and outcome of real reduction. 3D printing technique can significantly improve the outcome of calcaneal fracture surgery via providing a better pre-operation plan, and a training platform for residents and surgical teams to completely understand the open reduction and stable internal fixation procedures. A 3D printed model is excellent for the education of junior surgeons. 3D models offer insight to a patient's unique anatomy. Abstract: Background: It was aimed to compare conventional surgery and three-dimensional (3D) model-assisted surgery used in the treatment of calcaneal fractures. Materials & Methods: A total of 37 patients with unilateral calcaneal fractures were randomly divided into two groups as a conventional surgery group (n: 19) and a 3D model-assisted surgery group (n: 18). The preoperative, postoperative and last follow up angles of the Bohler and Gissane, calcaneal width and facet height were measured. The duration of the operation, blood loss volume, fluoroscopy usage, instrumentation time for both groups were recorded. Finally, the follow-up AOFAS scores were evaluated. A questionnaire was used to determine the perceptions of the resident doctors about the 3D model. Results: The duration of the operation, blood loss volume, fluoroscopy usage, instrumentation time for 3D model-assisted surgery group were 83.3 ± 4.6 minutes, 83.6 ± 4.6 ml, 6.8 ± 1.4 times and 13.0 ± 0.8 weeks, and as for conventional group they were 130.0 ± 5.8 minutes, 105.1 ± 5.6 minutes, 11.7 ± 1.5 ml, 22.2 ± 2.4 times and 13.3 ± 0.8 weeks, respectively ( p < 0.0001). The both groups significantly restored Bohler angle, Gissane angle, calcaneal width and calcaneal facet height after operation ( p < 0.0001). The 3D model-assisted group was significantly more succesful in restoration and protection of achieved correction of calcanel facet height ( p < 0.0001). The difference was determined among the groups at the final follow-up examination with respect to the amount of change according the values achieved post-op. were significant in Bohler angle ( p < 0.001), calcaneal facet height ( p < 0.0001) and calcaneal widht ( p = 0.017). There was no significant difference between AOFAS scores of the two groups at last follow-up. Resident doctors exhibited high scores of overall satisfaction with the use of a 3D printing model. Conclusions: Compared to the conventional group, the 3D model-assisted group provide successful intervention and reduce operation, instrumentation time and the fluoroscopy usage with less blood loss. Performing 3D-assisted surgery helps the quality of reduction during the surgery and stability of internal fixation to protect achieved reduction at follow-up more succesfully.